2022
DOI: 10.3389/fmed.2022.788228
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil (CellCept®) in Combination With Low Dose Prednisolone in Moderate to Severe Graves' Orbitopathy

Abstract: Although corticosteroids are currently the first-choice drug for thyroid eye disease (TED), in 20–30% of cases, patients show poor or non-existent responses, and when the drug is withdrawn, 10–20% of patients relapse. Thus, in this study, we aimed to investigate the efficacy of the combined use of mycophenolate mofetil (CellCept®) and low dose oral prednisolone in patients with moderate to severe Graves' orbitopathy (GO). For the first time, we investigated the relationship between TED-related parameters and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Mycophenolate has been used in a large number of patients, mostly for prevention of transplant rejection, and in patients with autoimmune diseases ( 105 ). The published experience in TED is limited to two RCTs ( 68 , 106 ), one nonrandomized trial ( 107 ) and one retrospective report ( 108 ).…”
Section: Management Of Moderate-to-severe Tedmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycophenolate has been used in a large number of patients, mostly for prevention of transplant rejection, and in patients with autoimmune diseases ( 105 ). The published experience in TED is limited to two RCTs ( 68 , 106 ), one nonrandomized trial ( 107 ) and one retrospective report ( 108 ).…”
Section: Management Of Moderate-to-severe Tedmentioning
confidence: 99%
“…A third study was a retrospective audit with a highly heterogeneous population of 20 patients with limited efficacy data and will not be considered any further ( 108 ). Finally, a recent nonrandomized trial examined the use of mycophenolate mofetil plus oral prednisolone in 242 patients with moderate-to-severe TED ( 107 ).…”
Section: Management Of Moderate-to-severe Tedmentioning
confidence: 99%
“…In addition, our study found that MMF reduced CAS more significantly in GO patients. It has been reported that MMF combined with low-dose prednisolone therapy could be introduced as a new optimal administration for GO due to its advantages in chronic complications such as proptosis and diplopia [ 30 ]. Finally, our results also showed that fewer AEs occurred with MMF compared to GC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, Graves' orbitopathy is resistant to treatment with steroids in 20%-60%, prompting the need for alternative therapies. 17 Fortunately, in children, Graves' orbitopathy is rarely as problematic and simple measures to lubricate and protect the cornea are sufficient. In the rare cases where orbitopathy is prominent, a referral to a specialised ophthalmology service would be suggested 18 Recommendation: All children with eye signs should be promptly referred to specialist paediatric ophthalmology services.…”
Section: Eye Signsmentioning
confidence: 99%